The substitution method is a direct way to solve two equations with two unknowns. To solve by substitution, first solve one of the equations for one variable, and substitute the result into the other equation. Plug the result into the second equation, and solve for the other unknown.
As a simple example, to solve the two equations x - y = 1 and x + y = 3, solve the first equation for either x or y. Solving for x by adding y to both sides results in x = y + 1. Substituting this in for x in the second equation gives (y + 1) + y = 3 or 2y = 2 and y = 1. Plugging that back into the first equation gives x - 1 = 1 or x = 2.